Optimization of yellowfin tuna (Thunnus albacares) viscera protein hydrolysate (YFTV FPH) antioxidants using central composite design (CCD). - Falalimpa, Alessandra, Nicole B.
Yellowfin tuna viscera (YFTV) fish protein hydrolysates (FPH) are valorized products from tuna processing wastes or discards with huge antioxidant capacities. Through optimization of alkaline protease (Enzaide®) hydrolysis condition, scaling up operations to mitigate the every-increasing fish wastes and produce antioxidant proteins is possible. This present study aimed at optimizing enzymatic hydrolysis conditions via Central Composite Design (CCD) of Response Surface Methodology (RSM) of Design Expert® with temperature (℃), time (h), and alkaline protease concentration (%) as independent variables. Ethanolic extract was prepared from the generated YFTV FPH, which was used for the assessment of the antioxidant properties of the sample using DPPH assay, FRAP assay, and ABTS assay. The total soluble protein content was also determined using the Bradford assay. The result of the study indicated that the optimum condition was 48.7℃ in 3.6 h at 3% enzyme concentration with a desirability value of 0.976. In this condition, the DPPH activity, FRAP activity, ABTS activity, and total soluble protein content were 54.22%, 0.322, 87.58%, and 0.35 mg/mL (p<0.05), respectively. The findings in this study could be used as a basis for optimizing tuna by-products with high antioxidant activity.